Motivasi Petani Dalam Usahatani Tumpang Sari Jagung Dan Kacang Tanah Di Desa Lailangga Kecamatan Wadaga Kabupaten Muna Barat - Azhar, La Ode Muhamad; Rianse, Usman; Batoa, Hartina (Fakultas Pertanian Universitas Halu Oleo, 2023)
Lailangga Village is one of the villages located in Wadaga District, West Muna Regency. Some of the people work in the agricultural sector, namely intercropping corn and peanuts. Of course, in farming, farmers have motivation in running their farming business which is known as the motivation to try. So this study aims to see the motivation of farmers in trying to intercrop corn and peanut. The location determination was done deliberately because the people of Lailangga Village are mostly working in the agricultural sector, especially farmers intercropping corn and peanuts. The population in this study was 372 farmers who cultivated corn and peanuts with a precision of 15% so that a sample of 41 people was obtained. This type of research is descriptive quantitative. Data analysis using class intervals. The results showed that farmers' motivation in managing farming both intrinsic (needs, hopes, interests) and extrinsic (family encouragement, environment and rewards) motivation were in the high category.